COMPREHENSIVE ANALYSIS OF STRENGTHENING PUBLIC HEALTH INFRASTRUCTURE AND STRATEGIES FOR COLLABORATION AND INNOVATION AMONG PUBLIC HEALTH PROFESSIONALS, HEALTH INSURANCE PROVIDERS, HEALTH MONITORING EXPERTS, PHARMACISTS, LABORATORY TECHNICIANS, AND ANESTHE - Ahmed Mohsen Ali Al Ishag, ‏Mohammed Mohsen Ali Al Ishaq, Jafar Mohammed A Al Ishaq, ‏Rubayan Yahya Rubayan Al Ishaq, ‏‏Mohammed Salem A Al Kubaybah, ‏‏Ishaq Ahmed Masoud Al Ishaq, ‏Yousef Mohammed Alqarih, ‏Mohsen Hussain Ali Alyami, (Chelonian Research Foundation, 2022)
A highly dependable public health infrastructure is essential and indispensable in these times of global health concerns.The healthcare of the country's populace is comprehensively addressed in this paper. The issues associated with strengthening public health infrastructure are addressed by looking at cooperation and innovativeness among various healthcare stakeholders, which include health professionals in public health, insurance providers, experts in health monitoring, pharmacists, laboratory technicians, and anesthesia technology experts. The analysis sets forth the current restraints as well as possibilities and recommendations to strengthen cooperation and innovation with the aim of generating beneficial public health outcomes. The research will approach this issue through a multidisciplinary methodology with the intention of providing practical information to policymakers, healthcare institutions, and professionals in charge of improving the public healthcare system. Keywords: public health, infrastructure, collaboration, innovation, healthcare,